River bank erosion assessment in the confluence of Thao, Da, and Lo rivers - Xuan, Pham Tich (Vietnam Journal of Earth Sciences, 2012)
River bank erosions in the confluence of Thao - Da - Lo rivers have been occurred and continuously develop. Our studies show that endogenous factors including right-slip movement of Red River Fault are underlying reason of the risks of river bank erosion and exogenous factors including morphology of river-bed, hydrological regime, characteristics of the river-bank constructed rocks and human activities play important roles in speeding up the process. Due to the geological and tectonic structures of the region, the river-bed development has northward tendency and risks of the riverbank erosion are unavoidable. Human activities just complicate these problems. Risks of river-bank erosion in the confluence of Thao - Da - Lo rivers are still very high, so there need suitable solutions to prevent possibly bad consequences.